PROBLEMATIC INTERNET USE: EXAMINING PARENTS-ADOLESCENT COMMUNICATION AND SELF-CONTROL WITH STRESS LEVEL AS MEDIATOR - Raihan 'Ainun Hasanah; Latifah, Melly; Krisnatuti, Diah (Jurnal Ilmu Keluarga dan Konsumen, 2023)
Although the internet can provide benefits and convenience for many users, it can lead to risky behaviors such as problematic internet use (PIU). This study investigates the relationship between parents-adolescent communication, self-control, and PIU mediated by stress levels. Data were collected from 233 Indonesian high school students selected using disproportionate stratified random sampling. The Parents-Adolescent Communication Scale, Brief Self-Control Scale, Depression Anxiety Stress Scale, and Problematic Internet Use in Adolescent were the scales used to measure the four variables. Descriptive analyses, difference test, Spearman correlations, structural equation modeling, and analysis of variance were used for data analysis purpose. The results show direct effects of openness in the parents-adolescent communication, self-control, and stress levels on PIU. Problems in parents-adolescent communication and self-control have an indirect effect on PIU as mediated by stress levels. These findings demonstrate the need for endeavors to urge adolescents to improve their self-control and manage stress levels to avoid PIU risk.